METHODOLOGY FOR DEVELOPING MATHEMATICAL SKILLS OF SCHOOL STUDENTS IN CIRCLE CLASSES (IN THE 7TH CLASS EXAMPLE) - Esanova Nazira Nazarovn (Journals Park Publishing, 2023)
In our country, great attention is paid to the creation of social, psychological, pedagogical and methodical conditions for the development of student's mathematical abilities. Because the mathematical preparation of young people is of particular importance in restoring the intellectual, creative and spiritual potential of our country, which implies not only the formation of mathematical knowledge, skills and abilities, but also the development of students' mathematical abilities.
Keywords: Textbook, ability, formula.